End-to-end performance of DF multihop hybrid RF/FSO system using MPPM coding and MIMO technique under dependent GG turbulence channels - Hechmi Saidi; Noureddine Hamdi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The paper presents a BER analysis for hybrid radio frequency/multihop free space optics, known as RF/FSO, communication system benefiting from multiple input multiple output (MIMO) configuration but impaired by gamma-gamma, known as GG, turbulence. Authors deploy Multiple Pulse Position Modulation, known as M-PPM, like a signaling technique. Furthermore, the exact as well as approximated amounts of symbol-error rates, known as SERs, are both judged in this work. A closed form formula related to the whole probability density function, called PDF, for our designed system is derived. Such interesting approach provides to us better quality of service by combating atmospheric turbulence.